Impact Survey Results after SAFE Strategy Implementation in 15 Local Government Areas of Kebbi, Sokoto and Zamfara States, Nigeria. (28th December 2018) - Mpyet, Caleb; Muhammad, Nasiru; Adamu, Mohammed Dantani; Ladan, Mohammad; Willis, Rebecca; Umar, Murtala Muhammad; Alada, Joel; Aliero, Aliyu Attahiru; Bakhtiari, Ana; Flueckiger, Rebecca Mann; Olobio, Nicholas; Nwosu, Christian; et al.
ABSTRACT: Purpose : To determine prevalence of trachoma after interventions in 15 local government areas (LGAs) of Kebbi, Sokoto and Zamfara States, Nigeria. Methods : A population-based impact survey was conducted in each LGA using Global Trachoma Mapping Project (GTMP) protocols. In each LGA, 25 villages were selected, except in Arewa LGA, where we selected 25 villages from each of four subunits to obtain finer-resolution prevalence information. Villages were selected with probability proportional to size. In each village, 25 households were enrolled and all consenting residents aged ≥1 year were examined by GTMP-certified graders for trachomatous inflammation—follicular (TF) and trachomatous trichiasis (TT). Information on sources of household water and types of sanitation facilities used was collected through questioning and direct observation. Results : The number of households enrolled per LGA ranged from 623 (Kware and Tangaza) to 2488 (Arewa). There have been marked reductions in the prevalence of TF and TT since baseline surveys were conducted in all 15 LGAs. Eight of the 15 LGAs have attained TF prevalences <5% in children, while 10 LGAs have attained TT prevalences <0.2% in persons aged ≥15 years. Between 49% and 96% of households had access to water for hygiene purposes within 1 km of the household, while only 10–59% had access to improved sanitation facilities. Conclusion : Progress towards elimination of trachoma has been made in these 15 LGAs. Collaboration with water and sanitation agencies and community-based trichiasis surgery are still needed in order to eliminate trachoma by the year 2020.